Feasibility Study on Marketing of Cultivated Medicinal and Aromatic Plants as Livelihood for Farmers in Harda and Dewas Districts of Madhya Pradesh, India - Bhattacharya, A. K.; Shekhar, Kunal; Kumar, Yogesh (Indian Forester, 2005)
The paper examines in detail various issues and factors influencing the marketing of the important cultivated medicinal and aromatic plants, viz Ashwagandha (Withania somnifera), Isabgol (Plantago ovata), Kalmegh (Andrographis paniculata), Lemon grass (Cymbopogon nardlls), Mentha (Mentha arvensis). Saf’ed Musli (Chlorophytum tllberosllm), Satawar (Asparaglls racemoslls), Senna (Cassia angllstifolia) in Madhya Pradesh. The paper also highlights the existing and potential marketing channels and the feasibility of effective marketing for these species inside and outside Madhya Pradesh.